Curing kinetics and mechanical properties of bio-based epoxy composites comprising lignin-based epoxy resins. (September 2016) - Ferdosian, Fatemeh; Zhang, Yongsheng; Yuan, Zhongshun; Anderson, Mark; Xu, Chunbao (Charles)
Graphical abstract: Highlights: Bio-epoxy systems were produced from various amounts of lignin-epoxy (25–100 wt%). Curing kinetics were evaluated by Kissinger and Friedman methods. Activation energy of the curing process depended on the content of lignin-epoxy resins. Bio-epoxy composites (<50–75 wt% lignin-epoxy) were exhibited great mechanical performance. Bio-epoxy films (<50 wt% lignin-epoxy) were showed high adhesion on metal substrate. Abstract: Lignin-based epoxy resins derived from de-polymerized Kraft/organosolv lignins were blended with a conventional bisphenol A (BPA)-based epoxy resin at various percentages to prepare bio-based epoxy systems as polymer matrices for manufacturing of fiber-reinforced plastics (FRPs) and coatings. The curing process of epoxy composites was studied using DSC and the activation energy was calculated by isoconversional methods. Epoxy composites comprising a low percentage (25 wt%) of lignin-based epoxy resin can be cured faster than the pure BPA-based epoxy resin used in particular at the early stage of curing. However, blending a large amount (>50 wt%) of lignin-based epoxy resin with the BPA-based epoxy resin retarded the curing process particularly at the late stage of curing. Tensile and flexural strengths of the prepared FRPs using bio-based epoxy composites were found to be superior or comparable to those of the FRP with the pure BPA-based epoxy resin when the lignin-based epoxy resin blending ratio is less than 50–75 wt%. Furthermore, the bio-based epoxy films comprising up to 50 wt% of DOL-based epoxy resin were exhibited high adhesion strength on a metal substrate.